A new species of Lopholeucaspis (Hemiptera: Diaspididae) from China, with a key to the species worldwide - Shen, Xuejie; Xue, Jinying; Zhao, Qing; Niu, Minmin; Wei, Jiufeng (Zootaxa, 2025)
A new species of armored scale insect (Hemiptera: Coccomorpha: Diaspididae), Lopholeucaspis taiguensis Shen & Wei sp. nov., is described and illustrated from China, based on the morphology of adult females, second-instar females and adult males. A key to the adult females of all the species of Lopholeucaspis is provided.